Amniotic fluid mesenchymal stem cells repair mouse corneal cold injury by promoting mRNA N4-acetylcytidine modification and ETV4/JUN/CCND2 signal axis activation - Xinfeng Fei; Yuying Cai; Feng Lin; Yongyi Huang; Te Liu; Yan Liu (Human Cell, 2021)
Severe corneal injury is one of the main causes of loss of visual function. Mesenchymal stem cells (MSCs) have the ability to repair damaged cells in vivo. The present study aimed to explore whether MSCs could function as a cell therapy tool to replace traditional methods to treat corneal injury. CD44 + /CD105 + mesenchymal stem cells isolated from mouse amniotic fluid (mAF-MSCs) were injected into mice after cryoinjury to induce corneal endothelial cell injury. Histopathological assays indicated that mAF-MSCs could promote the growth of corneal epithelial cells, reduce keratitis, and repair the corneal damage caused by low temperature. cDNA microarray analysis revealed that the mAF-MSCs affected the expression patterns of mRNAs related to cell proliferation and differentiation pathways in the mice after transplantation. The results of quantitative real-time PCR and western blotting revealed that NAT12, NAT10, and the ETV4/JUN/CCND2 signaling axis were elevated significantly in the mAF-MSC-transplantation group, compared with those in the phosphate-buffered saline-treated groups. High performance liquid chromatography–mass spectroscopy results revealed that mAF-MSCs could promote mRNA N4-acetylcytidine (ac4C) modification and high expression of N -acetyltransferase in the eyeballs. RNA immunoprecipitation-PCR results showed that a specific product comprising Vegfa , Klf4 , Ccnd2 , Jun , and Etv4 mRNA specific coding region sites could be amplified using PCR from complexes formed in mAF-MSC-transplanted samples cross-linked with anti-ac4C antibodies. Thus, mouse amniotic fluid MSCs could repair the mouse corneal cold injury by promoting the ETV4/JUN/CCND2 signal axis activation and improving its stability by stimulating N4-acetylcytidine modification of their mRNAs.